Biblical Symbolism of the Temple - Nereparampil, Lucius (Journal of Dharma, 1984)
The Temple has always been a place of peace and consolation for the human mind troubled by stresses and strains of worldly cares and worries. It is a place where man learns to transcend the level of his material existence and spring upward to commune with the other— worldly Reality. The fact that generally temples were all built on hills and mountains symbolically bears witness to this truth. The very structure of the Indian temple with its spire pointing to heaven is indicative of the heavenward rising up of the human spirit in search of union with the Divine. The Ziggurat temples of ancient Mesopotamia with their terrace platforms tending to reach up to heaven, represented the sacred place of communion between man from below and God from above, who descends stepping down from his heavenly abode to the earth below through those terrace platforms to meet man. In the Bible too we find references to the Temple. There the concept of the Temple reflects the faith and ideology of the ancestors of the Hebrews as well as of the Christians. A view of the Temple from the view point of biblical man, we hope, will enrich the understanding of the symbolism of the Temple, which has always been very central in the faith and praxis of all the world-religions.